Pandemia de COVID-19: espiritualidade/religiosidade entre médicos infectologistas - Silva, Cassiano Augusto Oliveira da (2024)
The general objective of this research is to: “understand whether Spirituality and Religiosity (E/R) influenced the life of infectious disease professionals and had an impact on the health care of seriously ill patients suspected and/or confirmed of COVID-19 in the period of the pandemic”. The main hypothesis of this is that: “the majority of infectious diseases doctors who worked in the health care of suspected and/or confirmed COVID-19 patients, during the pandemic period, found E/R relevant in their daily lives, especially in labor aspects”. This is an exploratory study, with a cross-sectional method and a qualitative-quantitative approach. For data collection, a script of semi-open questions was used, organized into blocks of objective questions addressing the following aspects: socio-demographic characteristics; Satisfaction with Life Scale (ESV- 5 items); Spiritual Malaise; Brief Spiritual/Religious Coping Scale – SRCOPE-14; centrality of religiosity and; beliefs and attitudes. In addition to a block of ten subjective questions, triggering beliefs, which covered the psychological effects of the pandemic on the world population; the role of spirituality in times of the COVID-19 pandemic; and the meaning of life and production of meaning. Quantitative data were tabulated, calculated, categorized, and analyzed using IBM SPSS software (version 24). Descriptive statistics (minimum and maximum values, mean, standard deviation, absolute frequencies, and percentages) were performed to characterize the sample and to outline the profile of participants in the evaluated constructs. Spearman’s Rô display coefficients and point biserial correlation were calculated to investigate the relationships between the analyzed variations. Used as significance level p < 0.05 for all inferential statistics. The Iramuteq software processed the information obtained from the interviews. There were 20 research participants, the majority were female (f = 15; 75%), aged between 34 and 60 years old (m = 43.5; SD = 7.05). The majority were married (f = 18; 90%), resident in the city of João Pessoa, PB (f = 18; 90%), with a monthly income of more than 8 minimum wages (f = 18; 90%), with postgraduate -graduation (f = 17; 85%) and self-declared white skin color (f = 14; 70%). At the time of collection, 45% had been infected with the COVID-19 virus and all took two doses of the vaccine and a booster dose. The majority stated that they were spiritual, but not religious (f = 6; 33%) and Catholic (f = 16; 80%). In general, the instruments showed high levels of satisfaction with life, positive coping, feelings of fear, and negative emotions during the pandemic. On the other hand, participants showed low levels of religious struggles, negative coping, religious explanations of the pandemic, and the impact of the pandemic on spirituality. The proposed hypothesis was confirmed, showing, in its originality, that doctors resorted to E/R to maintain their mental health. E/R plays an important role in controlling emotions during stressful situations and promoting health, well-being, and quality of life.